New challenges for innovation systems: a cross-country comparison. (1st January 2003) - Harding, Rebecca
This paper provides a cross-country comparison of science funding systems and policies to stimulate knowledge transfer across eight developed countries. In particular, strategies to connect processes of knowledge generation with final commercialisation of science within innovation systems are investigated. The analysis includes an overview of empirical results as well as an outlook on further developments in the methodology of assessing the effectiveness of knowledge transfer policies.